Preexposure prophylaxis for men who have sex with men in the Netherlands: impact on HIV and Neisseria gonorrhoeae transmission and cost-effectiveness. (15th March 2020) - Reitsema, Maarten; Hoek, Albert Jan van; van der Loeff, Maarten Schim; Hoornenborg, Elske; van Sighem, Ard; Wallinga, Jacco; van Benthem, Birgit; Xiridou, Maria
Abstract : Objectives: To assess the impact of a preexposure prophylaxis (PrEP) programme for high-risk men who have sex with men (MSM), which includes gonorrhoea testing and treatment, on the transmission of HIV and Neisseria among MSM in the Netherlands and the cost-effectiveness of such programme with and without risk compensation (in the form of reduced condom use). Methods: We developed a stochastic agent-based transmission model of HIV and gonorrhoea. We simulated a capped (max 2.5% of MSM) and uncapped (5.5% of MSM in 2018 declining to 3% in 2027) daily PrEP programme for high-risk MSM, with 3-monthly HIV and gonorrhoea testing, with and without risk compensation. Epidemiological outcomes were calculated from the transmission model and used in an economic model to calculate costs, quality-adjusted life-years (QALY), and incremental cost-effectiveness ratios (ICER), over 2018–2027, taking a healthcare payer perspective. Results: Without risk compensation, PrEP can lead to a reduction of 61 or 49% in the total number of new HIV infections in 2018–2027, if the programme is uncapped or capped to 2.5% of MSM, respectively. With risk compensation, this reduction can be 63 or 46% in the uncapped and capped programmes, respectively. In all scenarios, gonorrhoea prevalence decreased after introducing PrEP. Without risk compensation, 92% of simulations were cost-effective (of which 52% cost-saving). With risk compensation, 73% of simulations were cost-effective (of which 23% was cost-saving). Conclusion: A nationwide PrEP programme for high-risk MSM can result in substantial reductions in HIV and gonorrhoea transmission and be cost-effective, even with risk compensation. Abstract : Supplemental Digital Content is available in the text